2003
DOI: 10.1016/s0896-6273(03)00124-7
|View full text |Cite
|
Sign up to set email alerts
|

APP Processing and Synaptic Function

Abstract: A large body of evidence has implicated Abeta peptides and other derivatives of the amyloid precursor protein (APP) as central to the pathogenesis of Alzheimer's disease (AD). However, the functional relationship of APP and its proteolytic derivatives to neuronal electrophysiology is not known. Here, we show that neuronal activity modulates the formation and secretion of Abeta peptides in hippocampal slice neurons that overexpress APP. In turn, Abeta selectively depresses excitatory synaptic transmission onto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

85
1,252
5
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,437 publications
(1,351 citation statements)
references
References 66 publications
85
1,252
5
9
Order By: Relevance
“…13,14 In healthy brain, non-amyloidogenic and amyloidogenic processing are balanced, with Ab peptides being important effectors in synaptic transmission and plasticity. 15,16 In 2003, Yang et al reported enhanced BACE1-mediated amyloidogenic cleavage in AD. 17 Recent evidence suggests that BACE1 activity can be elevated much earlier and may foster the conversion from mild cognitive impairment to AD.…”
Section: Role Of Bace1 In Admentioning
confidence: 99%
“…13,14 In healthy brain, non-amyloidogenic and amyloidogenic processing are balanced, with Ab peptides being important effectors in synaptic transmission and plasticity. 15,16 In 2003, Yang et al reported enhanced BACE1-mediated amyloidogenic cleavage in AD. 17 Recent evidence suggests that BACE1 activity can be elevated much earlier and may foster the conversion from mild cognitive impairment to AD.…”
Section: Role Of Bace1 In Admentioning
confidence: 99%
“…Kamenetz and coworkers demonstrated that increased synaptic activity enhanced the formation and secretion of A β peptide in hippocampal slice neurons (Kamenetz et al , 2003 ). In turn, A β selectively depresses excitatory synaptic transmission onto neurons that overexpress APP as well as nearby neurons that do not.…”
Section: App Metabolism and A β Formationmentioning
confidence: 99%
“…6,7 Release of the extracellular domain of APP from presynaptic terminals has been observed in response to electrical activity. 8 This domain, in turn, regulates neuronal excitability 1 and enhances proliferation of progenitor cells in the subventricular zone. 9 Not only is the intracellular domain of APP of functional importance, but the proteolytic fragments derived from the extracellular domain are also of interest.…”
Section: Introductionmentioning
confidence: 99%